The Development of Plasmodium falciparum-Specific IL10 CD4 T Cells and Protection from Malaria in Children in an Area of High Malaria Transmission - Boyle, Michelle J.; Jagannathan, Prasanna; Bowen, Katherine; McIntyre, Tara I.; Vance, Hilary M.; Farrington, Lila A.; Schwartz, Alanna; Nankya, Felistas; Naluwu, Kate; Wamala, Samuel; Sikyomu, Esther; Rek, John; et al. (Frontiers in Immunology, 2017)
Cytokine-producing CD4 T cells have important roles in immunity against Plasmodium falciparum (Pf) malaria. However, the factors influencing functional differentiation of Pf-specific CD4 T cells in naturally exposed children are not well understood. Moreover, it is not known which CD4 T cell cytokine producing subsets are most critical for protection. We measured Pf-specific IFNγ-, IL10- and TNFα-producing CD4 T cell responses by multi-parametric flow-cytometry in 265 children aged 6 months to 10 years enrolled in a longitudinal observational cohort in a high malaria transmission site in Uganda. We found that both age and parasite burden were independently associated with cytokine production by CD4 T cells. IL10 production by IFNγ+ CD4 T cells was higher in younger children and in those with high parasite burden during recent infection. To investigate the role of CD4 T cells in immunity to malaria, we measured associations of Pf-specific CD4 cytokine-producing cells with the prospective risk of P. falciparum infection and clinical malaria, adjusting for household exposure to Pf-infected mosquitos. Overall, the prospective risk of infection was not associated with the total frequency of Pf-specific CD4 T cells, nor of any cytokine-producing CD4 subset. However, the frequency of CD4 cells producing IL10 but not inflammatory cytokines (IFNγ and TNFα) was associated with a decreased risk of clinical malaria once infected. These data suggest that functional polarization of the CD4 T cell response may modulate the clinical manifestations of malaria and play a role in naturally acquired immunity.